On the second Bogolyubov theorem for systems with random perturbations - Stanzhitskii, A. N. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
For systems of differential equations with random right-hand sides, we establish conditions for the existence of periodic solutions in the neighborhoods of equilibrium points of the averaged system.